Comparisons of the abundance and vertical distribution of zooplankton between upwelling and non-upwelling areas off the Zamboanga Peninsula, East Sulu Sea - Acabado, Cristy S. (Mag-ao, Iloilo University of the Philippines Visayas, 2011)
Partially enclosed marine basins often display characteristic faunal composition reflecting their distinctive hydrographic conditions. Seasonal upwelling events in the east Sulu Sea influence zooplankton abundance, which result to the high fisheries production in the area. Zooplankton in the East Sulu Sea were investigated during the Joint PhilEx oceanographic cruise on board the R/V Melville in December 2007. Data on the abundance and vertical distribution of major groups of zooplankton were analyzed and compared between three sets of MOCNESS samples : upwelling and non-welling stations, 11km and 72 km off the coast of Zamboanga Peninsula, respectively, and another non-welling station near Dipolog Strait. Comparisons of physical factors such as temperature, salinity and dissolved oxygen showed slight differences, but were consistent with a weak upwelling in the coastal station. A total of 107 taxa from 25 major groups of zooplankton were identified. The total zooplankton density was highest in the coastal station (593.7 ind./m3) than in the offshore station (379.5 ind./m3) and the station near Dipolog Strait (589.6 ind./m3). Coperods dominated in all stations comprising up to 0% of the total zooplankton. ANOSIM results separated the upwelling station from the other two stations and might be due to the dominance of ubiquitous taxa in the former. SMPER showed the highest dissimilarity between depths in the upwelling station, which is also consistent with a weak upwelling. Zooplankton distribution was discussed further and compared to oceanographic conditions that drive such patterns.
Thesis (M. S. Biology) -- Miagao, Iloilo : U. P. Visayas, October 2011.